Entre o semear e o vender: a batata-doce sob o amargor da subordinação camponesa em Sergipe - Lima, Mara Íris Barreto (2023)
This dissertation comprises the results of an analysis of peasant subordination in the production of sweet potatoes for the capitalist market in the agrarian space of Agreste Central Sergipano and in the municipality of Riachuelo. The objectives of the research were to analyse the subjection of peasant income in the production of sweet potatoes for the market, in the context of the expansion of capitalist production relations in the countryside; to debate the peasantry as a class and social subject in movement, considering the particular nuances of the Agrarian Question in a state with a concentrated land structure and a strong presence of smallholdings, in which food production is dominant; and to highlight the forms of organization of the peasantry and the strategies for appropriating income in the research area. In addition to reproducing themselves from the product of their labor, the peasantry has been compelled to produce goods and, in this context, there is a growing demand for production for the market, which places workers in a situation of subjection to capital, while reducing their autonomy in dealing with the land and producing diversified crops. This situation, present in the cultivation of sweet potatoes in Sergipe, especially in the municipalities of Moita Bonita, Itabaiana, Malhador and Riachuelo, is made worse by the predominance of smallholdings, which are often divided up in different ways (sale of land, division by inheritance and/or by the lending system). According to these data, more than 80% of the peasant family production units in the municipalities with sweet potatoes have an area of less than 10 hectares and more than 60% have an area of less than 2 hectares. The monopolization of production and the difficulty of diversifying crops due to the size of the property are conditions that require direct producers to organize themselves in order to secure an income. In this sense, cooperatives appear to be an important strategy in the face of the challenges imposed by the market. However, the movement of the contradiction creates and reproduces different determinations, because the subjection of the peasantry to capital still persists, which advances by creating new power relations in an unequal and articulated way, like a germ that tries to deny the historical condition of the peasant class. This framework, under the sieve of dialectics, allows us to understand the production of Sergipe's agrarian space as a simulacrum of capitalist relations, the peasant forms of reproduction and the levels of reaffirmation of the commodity, a scenario in which subordination occurs in food production. However, we also understand the importance of the peasant's permanence through his work, as a historical subject of struggle, showing us how it is possible for him to reproduce socially on the land, which is an expression of his territory of life.